Pengaruh Variasi Tinggi Tumpukan Pada Proses Pengomposan Limbah Lumpur Sawit Terhadap Termofilik - Hatflan Erico Rambe; Elvi Yenie; Ivnaini Andesgur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Palm Oil Mill Effluent treatment produces sludge as byproduct. The sludge produced will cause problems for environment if there are no actions and treatments taken toward the sludge. The purpose of this research is to reduce the pollution of palm oilmill effluent with aerob composting methods using sludge, boiler ash and palm oil fiber. The instrument used is a simple composter with 60 cm height and 30 cm diameter. The sludge is mixed with boiler ash, fiber and organic waste, and then EM-4 was added as an activator. This research used the addition of 0,7 % EM-4activator, with variations of stack’s height are 40, 45 and 50 cm to find out the optimal height to achieve thermophylic condition and the quality of the compost produced. The result of this research shows that compost with 50 cm stack’s height reached the highest temperature of 47,30C. The quality of the compost produced meets the SNI’s 19-7030-2004 requirement. The compost is mature at the 21st day with result Rasio C/N= 12,2. The conversion of palm’s oil sludge into compost can beused as an alternative in utilization waste into valuable product.Keywords: boiler ash, compost, EM-4 activator, fiber, palm’s sludge